ECONOMIC LITERACY AND PRICE OF GOODS CONCEPT IN SAMPE CITA VILLAGE FOR HOUSEHOLD BUSINESS GROUP - Dewi Mahrani Rangkuty; Andi Setiawan; Riska Franita; Resti Triana Ningsih (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2024)
Economic literacy is an individual's ability to understand, analyse and use economic information in everyday life. And the price of goods is the amount of money that must be paid by consumers to obtain a good or service. The purpose of this service activity is to educate the concept of economic literacy and the price of goods in the Sampe Cita village household business group. The method of implementation is through lectures, questions and answers, problem discussions, which then evaluate the productivity of the household business group in question. What is a follow-up in this service activity, in addition to evaluating the productivity of the Sampe Cita village household business group, there will be a next stage of educational activities on different concepts as a provision of understanding if it is still a problem in order to increase the productivity of the business group. Thank you to the Village Head and Village Officials who have supported the implementation of this service activity and it is hoped that they will always support the service activities in the next stage.